2016
DOI: 10.1038/srep24077
|View full text |Cite
|
Sign up to set email alerts
|

90Sr in teeth of cattle abandoned in evacuation zone: Record of pollution from the Fukushima-Daiichi Nuclear Power Plant accident

Abstract: Here we determined the 90Sr concentrations in the teeth of cattle abandoned in the evacuation area of the Fukushima-Daiichi Nuclear Power Plant (FNPP) accident. 90Sr activity concentrations in the teeth varied from 6–831 mBq (g Ca)−1 and exhibited a positive relationship with the degree of radioactive contamination that the cattle experienced. Even within an individual animal, the specific activity of 90Sr (Bq (g Sr)−1) varied depending on the development stage of the teeth during the FNPP accident: teeth that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Figure 5.2 shows the relationship between 90 Sr activity concentration in hard tissues (teeth and mandibular bones) of cattle and in soil from the ex-evacuation zone (Okuma Town and Kawauchi Village) after the FNPP accident. Activity concentrations of 90 Sr in the teeth were 150-830 mBq/g Ca (ratio of 90 Sr radioactivity to Ca weight in the tooth) (average, 470 mBq/g Ca) for Okuma Town and 100-310 mBq/g Ca (average, 170 mBq/g Ca) for Kawauchi Village [17]. The deposited amount of 90 Sr in soil was 94-1500 Bq/m 2 (average, 740 Bq/m 2 ) for Okuma Town and 39-380 Bq/m 2 (average, 200 Bq/m 2 ) for Kawauchi Village [9].…”
Section: Sr Activity Concentration In the Hard Tissue Of Abandonedmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 5.2 shows the relationship between 90 Sr activity concentration in hard tissues (teeth and mandibular bones) of cattle and in soil from the ex-evacuation zone (Okuma Town and Kawauchi Village) after the FNPP accident. Activity concentrations of 90 Sr in the teeth were 150-830 mBq/g Ca (ratio of 90 Sr radioactivity to Ca weight in the tooth) (average, 470 mBq/g Ca) for Okuma Town and 100-310 mBq/g Ca (average, 170 mBq/g Ca) for Kawauchi Village [17]. The deposited amount of 90 Sr in soil was 94-1500 Bq/m 2 (average, 740 Bq/m 2 ) for Okuma Town and 39-380 Bq/m 2 (average, 200 Bq/m 2 ) for Kawauchi Village [9].…”
Section: Sr Activity Concentration In the Hard Tissue Of Abandonedmentioning
confidence: 98%
“…We previously reported activity concentration and specific activity of 90 Sr in the teeth of cattle stayed in the ex-evacuation zone (Fig. 5.1) of the FNPP accident [17]. Because of chemical similarity between Sr and calcium (Ca), the teeth incorporate Sr during their formation period (calcification period) and retain it until they fall out or are worn down.…”
Section: Sr Activity Concentration In the Hard Tissue Of Abandonedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fukushima Daiichi nuclear power plant (FDNPP) accident drew global attention to the health risks of radiation exposure. We have established an archive system composed of livestock and wild animals within a 20 km radius from FDNPP, that is, the ex-evacuation zone of the FDNPP accident [1][2][3][4][5][6][7][8][9][10][11][12][13]. This system provides critical information for the understanding of environmental pollution, biodistribution, radionuclide metabolism, dose evaluation, and the biological effects of internal and external exposure to radiation caused by nuclear disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Although our sperm data is negative, the data presentation of no abnormality would be an important milestone to study the risk evaluation of human safety. Furthermore, we detected the existence of 90 Sr in teeth tissue of cattle, indicating the scientific evidence that 90 Sr was also released from the FNPP accident (Koarai et al., 2016). Our research group showed the existence of double‐strand break DNA damage in lymphocyte cells derived from the abandoned cattle, which were detected by the immune‐staining of gamma‐H2AX foci (Nakamura et al., 2017).…”
Section: Introductionmentioning
confidence: 99%